2016
DOI: 10.1016/j.bbamem.2015.10.015
|View full text |Cite
|
Sign up to set email alerts
|

In situ and real time investigation of the evolution of a Pseudomonas fluorescens nascent biofilm in the presence of an antimicrobial peptide

Abstract: Against the increase of bacterial resistance to traditional antibiotics, antimicrobial peptides (AMP) are considered as promising alternatives. Bacterial biofilms are more resistant to antibiotics that their planktonic counterpart. The purpose of this study was to investigate the action of an AMP against a nascent bacterial biofilm. The activity of dermaseptin S4 derivative S4(1-16)M4Ka against 6 h-old Pseudomonas fluorescens biofilms was assessed by using a combination of Attenuated Total Reflectance-Fourier … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 64 publications
7
42
0
Order By: Relevance
“…The above-mentioned techniques are simple and reproducible, but do not fully capture in vivo conditions (Macià et al, 2014). The flow cell system is a more sophisticated method for evaluating antibiofilm activity (de la Quilès et al, 2016). In this technique, biofilms are grown in flow cell chambers in the presence of HDPs at specific concentrations and imaged non-destructively using confocal laser scanning microscopy (CLSM) or Attenuated Total Reflectance-Fourier Transform Infrared (ATR-FTIR) spectroscopy (Quilès et al, 2016).…”
Section: Minimum Biofilm Inhibitory Concentrationmentioning
confidence: 99%
“…The above-mentioned techniques are simple and reproducible, but do not fully capture in vivo conditions (Macià et al, 2014). The flow cell system is a more sophisticated method for evaluating antibiofilm activity (de la Quilès et al, 2016). In this technique, biofilms are grown in flow cell chambers in the presence of HDPs at specific concentrations and imaged non-destructively using confocal laser scanning microscopy (CLSM) or Attenuated Total Reflectance-Fourier Transform Infrared (ATR-FTIR) spectroscopy (Quilès et al, 2016).…”
Section: Minimum Biofilm Inhibitory Concentrationmentioning
confidence: 99%
“…To address this challenge, we need experimental approaches that allow us to directly probe how metabolites affect microbial cells, ideally in situ and in real time. One such method is Attenuated Total Reflectance-Fourier Transform InfraRed (ATR-FTIR) spectroscopy, which was recently applied to gain insight into the molecular mechanism of action of an antimicrobial peptide (dermaseptin) against Pseudomonas fluorescens biofilms [67]. This study revealed that dermaseptin led to a loss of membrane lipids and a rapid inhibition of nucleic acid biosynthesis in young P. fluorescens biofilms [67].…”
Section: Conclusion: Challenges and Opportunitiesmentioning
confidence: 99%
“…One such method is Attenuated Total Reflectance-Fourier Transform InfraRed (ATR-FTIR) spectroscopy, which was recently applied to gain insight into the molecular mechanism of action of an antimicrobial peptide (dermaseptin) against Pseudomonas fluorescens biofilms [67]. This study revealed that dermaseptin led to a loss of membrane lipids and a rapid inhibition of nucleic acid biosynthesis in young P. fluorescens biofilms [67]. ATRFTIR thus can be used to probe and monitor, in situ and in real time, the biochemical changes induced by antibiotics in bacteria cells at the molecular scale during early biofilm formation.…”
Section: Conclusion: Challenges and Opportunitiesmentioning
confidence: 99%
“…Based on these results, carbon source can be used as a process lever to tune the porosity and composition of the biofilms, which would also have a direct bearing on the mechanical properties. These biofilms are natural, biodegradable and sustainable materials that can find applications as membranes for wastewater treatment (Shukla et al ; Quilès et al ), and wound care materials (Smith et al ; Suarato et al ), which require flexible ‘housing’ and a highly porous structures for exchange of fluids.…”
Section: Discussionmentioning
confidence: 99%
“…These biofilms are natural, biodegradable and sustainable materials that can find applications as membranes for wastewater treatment (Shukla et al 2014;Quil es et al 2016), and wound care materials (Smith et al 2016;Suarato et al 2018), which require flexible 'housing' and a highly porous structures for exchange of fluids.…”
Section: Discussionmentioning
confidence: 99%